Periprosthetic joint infections – a scoping review - Youssef Yasmin; Hättich Annika; Klepka Kim Lydia (Innovative Surgical Sciences)
Periprosthetic joint infections (PJIs) are dramatic complications after primary total joint arthroplasty. Despite increasing research in this field, the diagnosis, classification, and management of PJI remain a challenge. This is mainly due to the heterogenous clinical presentation of PJI in clinical routine and patient-related factors as secondary diagnosis and periprosthetic tissue condition. The early detection of PJI is essential for adequate treatment. However, there is no definition for PJI with 100 % sensitivity or a negative predictive value. This can potentially lead to a delayed or missed diagnosis of PJI. Furthermore, the surgical and antibiotic treatment is among the most discussed topics in PJI literature. There is no international consensus on the treatment of different PJI entities. Concludingly many aspects of PJI diagnostics and treatment remain controversially discussed and current studies are only comparable to a limited extent due to study heterogeneity and limited comparability.